KAPASITAS TANTRA DALAM MENGELOLA KEMAMPUAN BERPIKIR - I Putu Suweka Oka Sugiharta (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Tantra is a very mature method because it gives serious attention to the mind. Tantra experts have understood that human success or failure in life comes from the mind. Success and failure include both worldly and spiritual aspects. In its application, Tantra directs the human mind on the steps of regulating the mind. Once the mind can be conditioned properly then life becomes harmonious. The method of regulating the mind makes Tantra not only imaged as a passive mystical practice. The purpose of this study was to get an overview of the role of Tantra in managing thinking skills. The method used is a qualitative method that combines literature review and reasoning so that it appears that Tantra makes a major contribution to the management of thinking skills. Tantra is further stated to accommodate humans as thinking beings, Tantra deserves to be declared as knowledge, and Tantra includes the basic thinking faculties